(untitled) (Homoeopathy for All, 2024)
Obsessive-compulsive disorder (OCD) is a relatively rare neurosis marked by persistent obsessions and compulsions, impacting approximately 2.5% of the population. Its prevalence stands at about 2.5% among the general population and less than 5% among psychiatric patients. Onset typically occurs in adolescence, often before the age of 30, and affects both genders equally. Individuals with above-average intelligence are most commonly affected.